Value Analysis Method For Cost Reduction Analysis of Fuel Filter Poducts at PT Duta Nichirindo Pratama - Suwandi, Suwandi; Hari Hadi, AGUS (AGUSPATI Research Institute, 2020)
This adult consumers has become an important pioneer in product sales and improvement of technology and rapid information makes consumers choose a quality product at a low price so that companies vying to create a quality product and competitive in the market so much in buying by consumers. So to get products have the same quality and product prices can cheap, is used method of value analysis, where this method refers to the replacement of good material, design, or child part that have been previously used but not reduce the main function of the product is so that it can reduce the price of the goods. The analysis showed that the product that changed in terms of this material can reduce the price of the product so that can be used to saving cost.